UJI BEBERAPA DOSIS ASAP CAIR BERBAHAN BAKU TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Yuningsih, Riris; Puspita, Fifi; ', Sampoerno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to observe the dose of liquid smoke made from palm oil empty fruit bunches best as organic fertilizer to support the growth of cocoa seedling. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau, Jl. Bina Widya km 12.5 Simpang Baru Village, Tampan District, Municipality of Pekanbaru. The experiment was conducted for 5  months, starts from Juli to November 2014. The research was conducted as experiments using Completely Randomized Design (CRD) non-factorial that consisting of 4 treatments and 3 replications. To see the differences between treatments tested Duncan New Multiple Range Test (DNMRT) at the 5% level. Parameters  were observed are seedling height, leaf number, leaf area, stem circumference, root crown ratio and dry weight of seedlings. Result of research have shown that smoke liquid application with various doses significantly affected for seedling height and leaf number parameters, whereas no real effect on leaf area parameters cacao seeds, cacao seedling stem circumference, dry weight ratio of roots and shoots of cocoa seedlings   Keywords: dosage, liquid smoke, cocoa seedlings.